Feasibility of intraprocedural integration of cardiac CT to guide left ventricular lead implantation for CRT upgrades. (10th February 2021) - Gould, Justin; Sidhu, Baldeep S.; Sieniewicz, Benjamin J.; Porter, Bradley; Lee, Angela W. C.; Razeghi, Orod; Behar, Jonathan M.; Mehta, Vishal; Elliott, Mark K.; Toth, Daniel; Haberland, Ulrike; Razavi, Reza; et al.
Abstract: Background: Optimal positioning of the left ventricular (LV) lead is an important determinant of cardiac resynchronization therapy (CRT) response. Objective: Evaluate the feasibility of intraprocedural integration of cardiac computed tomography (CT) to guide LV lead implantation for CRT upgrades. Methods: Patients undergoing LV lead upgrade underwent ECG‐gated cardiac CT dyssynchrony and LV scar assessment. Target American Heart Association segment selection was determined using latest non‐scarred mechanically activating segments overlaid onto real‐time fluoroscopy with image co‐registration to guide optimal LV lead implantation. Hemodynamic validation was performed using a pressure wire in the LV cavity (dP/dtmax) ). Results: 18 patients (male 94%, 55.6% ischemic cardiomyopathy) with RV pacing burden 60.0 ± 43.7% and mean QRS duration 154 ± 30 ms underwent cardiac CT. 10/10 ischemic patients had CT evidence of scar and these segments were excluded as targets. Seventeen out of 18 (94%) patients underwent successful LV lead implantation with delivery to the CT target segment in 15 out of 18 (83%) of patients. Acute hemodynamic response (dP/dtmax ≥ 10%) was superior with LV stimulation in CT target versus nontarget segments (83.3% vs. 25.0%; p = .012). Reverse remodeling at 6 months (LV end‐systolic volume improvement ≥15%) occurred in 60% of subjects (4/8 [50.0%] ischemic cardiomyopathy vs. 5/7 [71.4%] nonischemic cardiomyopathy, p = .608). Conclusion: Intraprocedural integration of cardiac CT to guide optimal LV lead placement is feasible with superior hemodynamics when pacing in CT target segments and favorable volumetric response rates, despite a high proportion of patients with ischemic cardiomyopathy. Multicentre, randomized controlled studies are needed to evaluate whether intraprocedural integration of cardiac CT is superior to standard care.